2009
DOI: 10.1002/btpr.258
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cultivation of human mesenchymal stem cells in a rotating bed bioreactor system based on the Z®RP platform

Abstract: Because the regeneration of large bone defects is limited by quantitative restrictions and risks of infections, the development of bioartificial bone substitutes is of great importance. To obtain a three-dimensional functional tissue-like graft, static cultivation is inexpedient due to limitations in cell density, nutrition and oxygen support. Dynamic cultivation in a bioreactor system can overcome these restrictions and furthermore provide the possibility to control the environment with regard to pH, oxygen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Another study by Diederichs et al demonstrated that adipose tissue-derived hMSCs cultured for 47 days under osteogenic conditions onto macroporous zirconium dioxide-based ceramic discs with a diameter of 65 mm (natural or hydroxyaptatite (HA)-coated) in rotating wall vessels (1 rpm) displayed increased cell proliferation and bone matrix synthesis and mineralization, as evidenced by glucose consumption and positive staining for osteocalcein, Alizarin red and von Kossa respectively [43]. However, no significant improvements were observed on the HA-coated scaffolds, indicating a role played by the biomaterial properties in bone tissue development under the investigated conditions.…”
Section: Rotating Wall Vessel Bioreactorsmentioning
confidence: 99%
“…Another study by Diederichs et al demonstrated that adipose tissue-derived hMSCs cultured for 47 days under osteogenic conditions onto macroporous zirconium dioxide-based ceramic discs with a diameter of 65 mm (natural or hydroxyaptatite (HA)-coated) in rotating wall vessels (1 rpm) displayed increased cell proliferation and bone matrix synthesis and mineralization, as evidenced by glucose consumption and positive staining for osteocalcein, Alizarin red and von Kossa respectively [43]. However, no significant improvements were observed on the HA-coated scaffolds, indicating a role played by the biomaterial properties in bone tissue development under the investigated conditions.…”
Section: Rotating Wall Vessel Bioreactorsmentioning
confidence: 99%
“…It was reported that nanostructure surface enhanced the proliferation and osteogenic differentiation of the MSCs on titanium [23][24][25][26] . However, few studies were reported about the hMSCs behavior on the TZP with different surfaces 27,28) . We assumed that the microand nano-topography may have suitable configurations for hMSCs behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various attempts have been reported to expand MSC in three-dimensional (3D) environments, based on suspension culture in the presence of dynamic flow [85,86], on microcarrier beads [87][88][89] or on a rotating bed bioreactor system [90,91]. Papadimitropoulos et al [94] developed a system for the proliferation of MSC which entirely bypasses the use of 2D surfaces by seeding and expanding fresh bone marrow preparations directly within the pores of 3D scaffolds under perfusion flow.…”
Section: Three-dimensional (3d) Systemmentioning
confidence: 99%